2019
DOI: 10.1002/maco.201810655
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization kinetics of chromium oxide, manganese oxide, and manganese chromium spinel at high temperatures in environments containing water vapor

Abstract: Performance degradation of solid oxide fuel cells due to chromium volatilization is a well‐investigated issue in the literature. Therefore, retention coatings were developed to distinctly reduce the chromium volatilization. One approach was by alloying with manganese to ferritic steels to form manganese chromium spinel which is reported to decrease chromium volatilization by 61–75%. In the present paper, the volatilization rates of pure manganese chromium spinel ceramics were examined as well as those of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…72−75 The degree of nonstoichiometry (δ) typically increases with temperature and oxygen partial pressure. 76 The Frenkel-and Schottky-type defects that occur in the MnO crystal structure create cation/anion vacancies that are balanced by the oxidation of some Mn 2+ species to Mn 3+ . 64,75 During coking with ethylene-steam, we hypothesize that these vacancies result in more active Mn 3+ sites that can reduce and release oxygen to gasify coke and/or coke precursors on the surface.…”
Section: Mno/mno X As Anticoking Surface and Coke Oxidation Catalystsupporting
confidence: 64%
See 1 more Smart Citation
“…72−75 The degree of nonstoichiometry (δ) typically increases with temperature and oxygen partial pressure. 76 The Frenkel-and Schottky-type defects that occur in the MnO crystal structure create cation/anion vacancies that are balanced by the oxidation of some Mn 2+ species to Mn 3+ . 64,75 During coking with ethylene-steam, we hypothesize that these vacancies result in more active Mn 3+ sites that can reduce and release oxygen to gasify coke and/or coke precursors on the surface.…”
Section: Mno/mno X As Anticoking Surface and Coke Oxidation Catalystsupporting
confidence: 64%
“…In our previous work, we have deposited coke onto a MnO powder catalyst and shown that it has considerably higher coke gasification activity (under steam and steam-H 2 mixtures) compared to a Cr 2 O 3 powder catalyst . Several studies have shown that MnO is a metal-deficient oxide with varying degrees of nonstoichiometry: Mn 1−δ O, where 0 < δ < 0.15. The degree of nonstoichiometry (δ) typically increases with temperature and oxygen partial pressure . The Frenkel- and Schottky-type defects that occur in the MnO crystal structure create cation/anion vacancies that are balanced by the oxidation of some Mn 2+ species to Mn 3+ . , During coking with ethylene-steam, we hypothesize that these vacancies result in more active Mn 3+ sites that can reduce and release oxygen to gasify coke and/or coke precursors on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The Cr 2 O 3 layer is not dense and H 2 O continues to react with Cr 2 O 3 . Especially in mixed gas environments (for instance O 2 + H 2 O), it is known that the reaction of Cr 2 O 3 with O 2 and H 2 O leads to further volatilization of chromia by the formation of CrO 2 (OH) 2 according to reaction IX [31,33,57] The volatilization rate is also reported to be enhanced when the chromia layer is porous [58]. However, in the low-p O2 humid atmosphere, it was reported for Fe10Cr and Fe20Cr exposed to Ar-7% H 2 O at 900 °C for 72 h that the formation of volatile Cr-oxy-hydroxide is not the main reason for the suppression of a protective chromia scale growth [31].…”
Section: Impact Of the Oxidizing Atmospherementioning
confidence: 99%
“…Reaction with the crucible is thoroughly informed for CoO (crucibles turn blue, which is the color of the Co doped alumina); however, we did not observe changes in the color of the alumina crucible after the reaction. On the other hand, MnO has been shown to be volatile between 850 and 1050 °C . It is sensible to think that volatilization increases with temperature and therefore at 1350 °C MnO might volatilize.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, MnO has been shown to be volatile between 850 and 1050 °C. 21 It is sensible to think that volatilization increases with temperature and therefore at 1350 °C MnO might volatilize.…”
Section: Methodsmentioning
confidence: 99%